Electronic Spectra of ortho-Substituted Phenols: An Experimental and DFT Study - Samuel Tetteh; Ruphino Zugle; John Prosper Kwaku Adotey; Andrews Quashie (Journal of Spectroscopy)
The electronic spectra of phenol, 2-chlorophenol, 2-aminophenol, and 2-nitrophenol have been studied both experimentally and computationally. The effect of the substituents on the solvatochromic behavior of the phenols were investigated in polar protic (methanol) and aprotic (dimethyl sulfoxide (DMSO)) solvents. The spectra of 2-nitrophenol recorded the highest red shift in methanol. The observed spectral changes were investigated computationally by means of density functional theory (DFT) methods. The gas phase compounds were fully optimized using B3LYP functionals with 6-31++G(d,p) bases set. The effects of the substituents on the electron distribution in the σ-bonds as well as the natural charge on the constituent atoms were analyzed by natural bond orbital (NBO) and natural population analysis (NPA). Second-order perturbation analyses also revealed substantial delocalization of nonbonding electrons on the substituents onto the phenyl ring, thereby increasing its electron density. Full interaction map (FIM) also showed regions of varying propensities for hydrogen and halogen bonding interactions on the phenols.